Cytomegalovirus retinitis followed by immune recovery uveitis in an elderly patient with rheumatoid arthritis undergoing administration of methotrexate and tofacitinib combination therapy. Issue 8 (August 2017) - Yanagisawa, Kunio; Ogawa, Yoshiyuki; Hosogai, Mayumi; Todokoro, Daisuke; Mitsui, Takeki; Yokohama, Akihiko; Kishi, Shoji; Handa, Hiroshi
Abstract: Cytomegalovirus (CMV) retinitis is an opportunistic ocular infection most commonly observed in patients infected with human immunodeficiency virus (HIV). We present a rare case of CMV retinitis that developed in a non-HIV patient with rheumatoid arthritis (RA). Over the preceding 5 months, a family doctor had been treating the 78-year-old male patient with a combination therapy of methotrexate (MTX) and tofacitinib (TOF). CMV retinitis occurred when the patient's CD4+ T cells were low (196 cells/μl), and preceded the onset of Pneumocystis pneumonia. MTX and TOF were stopped after the diagnosis of CMV retinitis. While intravenous and intravitreal ganciclovir administration significantly improved the CMV retinitis, uveitis developed 3 months later during the maintenance therapy with oral valganciclovir, concomitantly with the recovery of the CD4+ T cell counts. As we believed this uveitis was caused by the immune reconstitution mechanism, we treated the patient with a retrobulbar injection of corticosteroids. During the 6 months following the cessation of MTX and TOF, there was no flare-up of the RA. Cases of CMV retinitis and immune recovery uveitis in RA patients have been rarely reported in the literature. In the current case, the intensive immunosuppressive therapy in this elderly patient might have been the cause of this unusual opportunistic complication of RA.